Mucograft® reconstruction of a vermillion defect: A case report - Belinda Liu; Ryan Smit; Darren Wang; Richard Cobb (Elsevier, 2022)
Mucograft® is a porcine collagen matrix material used for repair of intraoral mucosal defects. However, its use for repair of the vermillion zone has not been reported. A technique of vermillion repair using Mucograft® as an alternative to wedge closures or mucosal advancement flaps is reported.